Modeling China's energy consumption behavior and changes in energy intensity - Ma, H.; Oxley, Leslie; Gibson, J.; Kim, B. (Pergamon, 2009)
China's demand for energy has grown to fuel its rapidly expanding industrial, commercial and consumer sectors. At the same time, China has become the second largest consumer of petroleum products having surpassed Japan for the first time in 2003. The environmental consequences of a continuation of these trends will have global implications. Government policies and consumers have become more environmentally aware, but the ability of governments to formulate policies has been hindered by the lack of data on inter-factor and inter-fuel substitution possibilities. In this paper Allen partial elasticities of factor and energy substitution, and price elasticities of energy demand are calculated for China's industrial economy using a two-stage translog cost function approach for the period 1995-2004. The results suggest that energy is substitutable with both capital and labor. Coal is significantly substitutable with electricity and slightly complementary with oil, while oil and electricity are slightly substitutable. China's energy intensity is increasing during the study period and the major driver appears to be due to the increased use of energy-intensive technology. © 2009 Elsevier Ltd. All rights reserved.